2020
DOI: 10.3390/diagnostics10030141
|View full text |Cite
|
Sign up to set email alerts
|

Novel Assessment of Urinary Albumin Excretion in Type 2 Diabetes Patients by Raman Spectroscopy

Abstract: Urinary albumin excretion remains the key biomarker to detect renal complications in type 2 diabetes. As diabetes epidemy increases, particularly in low-income countries, efficient and low-cost methods to measure urinary albumin are needed. In this pilot study, we evaluated the performance of Raman spectroscopy in the assessment of urinary albumin in patients with type 2 diabetes. The spectral Raman analysis of albumin was performed using artificial urine, at five concentrations of albumin and 24 h collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…This finding corroborated with those found in the literature. [34] Subsequently, they were located in the spectra of the patients' saliva samples to analyze the intensities according to the Raman bands identified.Table 3 shows the six experimental Raman bands described in the current study, those found in the literature, the relative percentage error, the absolute difference between them, and their molecular assignment. [34] The differences in the Raman shifts shown in Table 3 are due to the Raman signal filtering and fitting algorithms used for peak assignment After establishing the bands associated with albumin, the purpose was to locate them both in healthy individuals and periodontitis spectra patients (see Figure 6).…”
Section: Discrimination Of Patients With Periodontitis Based On Album...mentioning
confidence: 99%
See 2 more Smart Citations
“…This finding corroborated with those found in the literature. [34] Subsequently, they were located in the spectra of the patients' saliva samples to analyze the intensities according to the Raman bands identified.Table 3 shows the six experimental Raman bands described in the current study, those found in the literature, the relative percentage error, the absolute difference between them, and their molecular assignment. [34] The differences in the Raman shifts shown in Table 3 are due to the Raman signal filtering and fitting algorithms used for peak assignment After establishing the bands associated with albumin, the purpose was to locate them both in healthy individuals and periodontitis spectra patients (see Figure 6).…”
Section: Discrimination Of Patients With Periodontitis Based On Album...mentioning
confidence: 99%
“…[34] Subsequently, they were located in the spectra of the patients' saliva samples to analyze the intensities according to the Raman bands identified.Table 3 shows the six experimental Raman bands described in the current study, those found in the literature, the relative percentage error, the absolute difference between them, and their molecular assignment. [34] The differences in the Raman shifts shown in Table 3 are due to the Raman signal filtering and fitting algorithms used for peak assignment After establishing the bands associated with albumin, the purpose was to locate them both in healthy individuals and periodontitis spectra patients (see Figure 6). [12] The high concentration of albumin in the saliva of patients with periodontitis is caused by the leakage of this protein, associated with inflammation and osteological compromise of periodontal damage, as evidenced in clinical case reports.…”
Section: Discrimination Of Patients With Periodontitis Based On Album...mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the ability of Raman spectroscopy to detect urinary albumin, the authors propose a promising method for detecting T2DM noninvasively in future work. 56 Each of these independent studies are important for their potential to be used for the early identification of diabetes via the minimally invasive monitoring of biomarkers which have previously not been focused on.…”
Section: Monitoring Novel Biomarkers For Indicating Diabetesmentioning
confidence: 99%
“…In effect this label‐free technique provides a fast and cost effective surrogate index of a biosamples metabolomic profile and has been successfully used across a wide range of medical applications including immune cell identity [6], cytokine detection [7], malignancy [8,9] and nephrology [10–13]. The complimentary technique of attenuated total reflection Fourier‐transform infrared (ATR‐FTIR) has been assessed in ANCA‐associated vasculitis with promising results demonstrated [14]; however, the application Raman spectroscopy in vasculitis has not previously been reported.…”
Section: Introductionmentioning
confidence: 99%